THE MANIFESTATION OF MISOGYNY IN THE PICK ME BOY TREND ON TIKTOK INDONESIA - Wang, Ying; Elfira, Mina (International Review of Humanities Studies, 2024)
Misogyny is hatred, contempt, or prejudice against women or girls. It is a form of sexism used to keep women in a lower social status than men, thereby maintaining patriarchal social roles. Hegemonic masculinity is the most exalted configuration of gender practices that legitimizes patriarchy. This article draws on the framework of Raewyn Connell's theory of masculinity and Kate Manne's concept of misogyny to discuss the phenomenon of Indonesian TikTok videos with the hashtag “Pick Me Boy” or #Pick Me Boy. Pick Me Boy challenge traditional masculinity to gain women's attention, and then demean women if rejected. This article uses a qualitative research method to explore how the language expressions and comments in Pick Me Boy videos reflect the phenomenon of mixed masculinity and misogyny by collecting and analyzing videos imitating Pick Me Boy on TikTok. The findings show that Pick Me Boy parody videos on TikTok illustrate male competition for female attention, reinforce stereotypes of masculinity while embodying male misogyny and reinforcing sexist behavior. This study highlights the various ways in which the Pick Me Boy trend perpetuates misogynistic beliefs and practices, revealing the complex interplay between gender dynamics and social media in the Indonesian context.